SMART HAFIZ SEBAGAI MEDIA PEMBELAJARAN AL-QUR’AN & KEISLAMAN DI LINGKUNGAN KELUARGA - Lili Hastuti (LPSDI Bina Patria, 2024)
For Muslims, reading al-Qur’an is something important and mandatory because the Koran is a book and guide for Muslims. A surprising phenomenon is that the IIQ results in the KKL Program in 2022 for 25 Provinces in Indonesia, stated that 75.25 out of 3111 were categorized as not being able to read the Koran well. This is certainly the obligation of Muslims to change this. Moreover, children are future assets who will carry the future of Islam. Learning to read the Koran can be done using various media and methods. In the current digital era where there are children who are starting to become addicted to gadgets, Smart Hafiz is here as an offer to replace gadgets that are safer for the eyes, do not require a quota, and are more educational. Smart Hafiz contains 80% Islamic content and 20% general content. Among the descriptions of the contents of Smart Hafiz are; let's recite the Koran, let's recite the Koran, let's sing, stories, films, good morals, camera, touch and learn, one day one juz, prayer hours, hafiz point, and other menus, namely about related products. Based on the results of researchers' observations, the use of Smart Hafiz is only starting to be used by those in the upper middle class. In the Agung Indah Panongan Cluster, children who use Smart Hafiz have better mastery, especially the hijaiyah letters and how to read them and memorize the letters. As a result, when they recite the Koran at TPQ or TPA, they already know much more and can actually become tutors for their friends. But again, no media is perfect, including Smart Hafiz. So in this case, parents still have to accompany, control and supervise the child in playing & learning.